2019
DOI: 10.4236/cc.2019.74007
|View full text |Cite
|
Sign up to set email alerts
|

Structures, Lipophilicity, Dipole Moments, Acidity and Spectroscopic Properties of Non-Steroidal Anti-Inflammatory Drugs Diclofenac, Bromfenac and Amfenac: A Theoretical Study

Abstract: This work is a contribution of theoretical chemistry to the classification of some non-steroidal anti-inflammatory drugs (NSAIDs). Indeed, research on the efficacy of NSAIDs has shown that no NSAID is recognized as the most efficient anti-inflammatory drug. We have made a theoretical study of diclofenac, bromfenac and amfenac, in order to compare their efficacy from some physicochemical properties. To do this, we used the DFT and TD-DTF methods at the B3LYP/6-311+G(d, p) level theory. The lipophilicity study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, some constraints must be overcome, such as particle size and crystal morphology, where the lack of functional groups on the surface reduces adsorbate molecule removal efficiency. 73 The majority of studies have found that caffeine adsorption is more efficient in an acidic or neutral environment. Caffeine adsorption is relatively consistent in the pH range of 5-8, according to studies.…”
Section: Attachment Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some constraints must be overcome, such as particle size and crystal morphology, where the lack of functional groups on the surface reduces adsorbate molecule removal efficiency. 73 The majority of studies have found that caffeine adsorption is more efficient in an acidic or neutral environment. Caffeine adsorption is relatively consistent in the pH range of 5-8, according to studies.…”
Section: Attachment Mechanismmentioning
confidence: 99%
“…However, some constraints must be overcome, such as particle size and crystal morphology, where the lack of functional groups on the surface reduces adsorbate molecule removal efficiency. 73 …”
Section: Caffeine Adsorption and Affecting Parametersmentioning
confidence: 99%
“…Another substance of interest in this group is caffeine. Caffeine is reported to have a high dipole moment, which increases with the polarity of the solution [1,21,22]. The neutral charge on the nitrogen atom interacts electrostatically with any negatively polarised functional group, and like that observed with atenolol, strongly positively charged caffeine ions are probably also capable of ion exchange in zeolites.…”
Section: Author Copy • Author Copy • Author Copy • Author Copy • Author Copy • Author Copy • Author Copy • Author Copy • Author Copymentioning
confidence: 99%
“…Then the spectral studies of NSAIDs have been performed using TD-DFT at B3LYP/6-311G(d,p) level of theory in gas phase. TD-DFT is a reliable method for the excited state computation that provides accurate results [43][44][45]. To obtain the nature and energy of the singlet-singlet electronic transition, the prediction of the first 3 excited states are performed.…”
Section: Spectroscopic Propertiesmentioning
confidence: 99%